2020
DOI: 10.14366/usg.20072
|View full text |Cite
|
Sign up to set email alerts
|

Clinical applications of Doppler ultrasonography for thyroid disease: consensus statement by the Korean Society of Thyroid Radiology

Abstract: Doppler ultrasonography (US) is widely used for the differential diagnosis of thyroid nodules, metastatic cervical lymph nodes in patients with thyroid cancer, and diffuse parenchymal disease, as well as for guidance in various US-guided procedures, including biopsy and ablation. However, controversies remain regarding the appropriate use and interpretation of Doppler US. Therefore, the Korean Society of Thyroid Radiology organized a taskforce to develop a consensus statement on the clinical use of Doppler US … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 108 publications
(319 reference statements)
1
21
0
Order By: Relevance
“…Different enhancement modes are related to the corresponding pathologic mechanisms (40). Numerous studies (11,32,(41)(42)(43)(44) have demonstrated hypo-enhancement and heterogeneous enhancement are major features of malignancy thyroid nodules. Possible explanations were necrosis, calcification, fibrosis, and embolus formation within the tumor (43).…”
Section: Discussionmentioning
confidence: 99%
“…Different enhancement modes are related to the corresponding pathologic mechanisms (40). Numerous studies (11,32,(41)(42)(43)(44) have demonstrated hypo-enhancement and heterogeneous enhancement are major features of malignancy thyroid nodules. Possible explanations were necrosis, calcification, fibrosis, and embolus formation within the tumor (43).…”
Section: Discussionmentioning
confidence: 99%
“…Intranodular vascularity was observed in 16.7%–91.7% of malignant nodules and 30.7%–65.3% of benign nodules [ 13 64 97 98 99 100 101 ]. Although intranodular vascularity may predict malignancy risk, no consistent associations have been reported for vascularity patterns with malignancy risk [ 101 102 103 ]. Several studies have reported that intranodular vascularity did not predict malignancy risk and was not superior to gray-scale US alone for the prediction of malignancy risk in all thyroid nodules [ 35 101 ].…”
Section: Us Lexicon For Thyroid Nodulesmentioning
confidence: 99%
“…Two separate biopsies were taken from BTN for control purposes and cytological sampling was performed. The biopsies taken were reported cytopathological using the Bethesda classification (2). Volumetric measurements of the nodules were made with US examination.…”
mentioning
confidence: 99%
“…However, surgery may have undesirable effects such as nerve paralysis, long hospital stay, difficulty in reoperation, scarring, and permanent hypothyroidism/ hypoparathyroidism. [2][3][4][5] Medical suppression treatments of thyroid nodules are often unsuccessful and do not contribute to the disappearance of complaints such as a feeling of pressure on the neck and cosmetic problems. Moreover, undesirable effects such as atrial fibrillation and decreased bone density may occur.…”
mentioning
confidence: 99%